An Effect of Digital Payment Use on Generation Z Muslim Consumption Behavior in Majalengka Regency - Encu M Syamsul; Ayu Gumilang Lestari; Muhammad Adrian; Nawal Khoerunnisa (LP2M IAIN Palopo, 2025)
The purpose of this study is to see whether there is an influence of the use of digital payments on the consumption behavior of Generation-Z Muslims in Majalengka Regency. The method used in this study was quantitative with a sample of 100 respondents, the research questionnaire was distributed using the google form tool and the results were analyzed using SPSS 23 software. The results of this study show that the variables of digital payment use and the consumption behavior variables of Muslim G-Z have a positive and significant influence, the t-value is calculated as 2.231 > t table 1.98447 and sig 0.028 ≤ 0.05 where Ho is rejected and Ha is accepted. Therefore, it is concluded that there is a significant influence of digital payments on consumption behavior.